Mastering Lali Linux for advanced penetration testing : apply a proactive approach to secure your cyber infrastructure and enhance your pentesting skills /: apply a proactive approach to secure your cyber infrastructure and enhance your pentesting skills. (2022) - Velu, Vijay Kumar
No abstract available